2007
DOI: 10.1089/aid.2006.0039
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Peripheral Blood mtDNA Levels in Naive Patients Treated by Different Nucleoside Reverse Transcriptase Inhibitor Combinations and Their Association with Subsequent Lipodystrophy

Abstract: Nucleoside reverse transcriptase inhibitors (NRTIs) differ in the type and severity of adverse effects resulting from mitochondrial abnormalities. mtDNA in peripheral blood mononuclear cells (PBMCs) was measured during the first 12 months of different NRTIs combinations and its association with clinical lipodystrophy was estimated. Extended follow-up of a randomized trial, ALBI-ANRS 070, including antiretroviral naive patients was conducted. Total DNA was extracted from available cryopreserved PBMCs at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…Other in vitro and in vivo studies have provided evidence of differential effects of NRTIS and combinations [14-17, 23, 43, 49]. Our study provides support for these studies demonstrating different potentials of individual NRTIs to affect mitochondria [41, 46], and that specific NRTIs in combination may affect mitochondrial function differently than may be predicted by a single NRTI, (e.g.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Other in vitro and in vivo studies have provided evidence of differential effects of NRTIS and combinations [14-17, 23, 43, 49]. Our study provides support for these studies demonstrating different potentials of individual NRTIs to affect mitochondria [41, 46], and that specific NRTIs in combination may affect mitochondrial function differently than may be predicted by a single NRTI, (e.g.…”
Section: Discussionsupporting
confidence: 80%
“…Clinical signs and symptoms of MD may not be recognized in advanced HIV disease with marked elevations of HIV viral load treated with multiple antiretroviral medications. Expression of MD may be related to host mitochondrial haplotypes or other genetic characteristics [10, 11], defects in intergenomic communication such as mitochondrial DNA depletion syndromes [12], environmental influences including HIV infection [13, 14], and specific ARVs [14-17]. Mitochondrial toxicity due to NRTI use in HIV-infected adults has been reported with zidovudine (ZDV), lamivudine (3TC), and stavudine (d4T) [4, 17-23], and in children with didanosine (ddI) exposure [24, 25].…”
mentioning
confidence: 99%
“…The measurement of mitochondrial DNA and its function in PBMCs may be of value for the early prevention of these toxicities in treated patients with HIV infection. A significant number of studies have shown the association between the use of NRTIs and mtDNA depletion, as well as the association between low mtDNA levels and subsequent development of lipodystrophy in patients with HIV infection [2,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. On the other hand, it has also been suggested that mtDNA content in peripheral blood cells may not be an accurate biomarker of mitochondrial toxicity in lipoatrophic adipose tissue because of a poor correlation between this parameter and any other mitochondrial parameter, as well as because of the preservation of mtDNA-dependent mitochondrial functions despite severe mtDNA depletion [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…El caso 1 es un caso típico de una adolescente de 13 años con infección, con exposición acumulativa y prolongada a TARGA y con el agravante, como en otros casos históricos cuando escaseaban los antirretrovirales, del empleo habitual de fármacos más tóxicos como asociación d4T + ddI, que era la regla. Se ha descrito que los fenómenos más graves de lipodistrofia morfológica se asocian con la mayor duración del TARGA, con la pubertad y con el uso de d4T [19][20][21] , todos ellos presentes en nuestra paciente. En este caso, a pesar de realizar medidas higiénico-dietéticas y modificaciones de los antirretrovirales, llegando incluso a la interrupción del mismo, precisó finalmente fármacos hipolipidemiantes.…”
Section: Discussionunclassified